PELATIHAN KURIKULUM MERDEKA DI SMP ISLAM DDI SANGATTA - Rahmat, Ismail; Syafi’i, Muhammad Imam; Zahra, Zaitun (El-Madaniyah : Jurnal Pengabdian Masyarakat, 2024)
This community service aims to implement the Independent Curriculum at DDI Sangatta Islamic Middle School. Through a series of curriculum development activities, including training for teachers as well as the preparation of learning materials and methods in accordance with the principles of the Independent Curriculum. The methods used include observation, interviews and discussions with stakeholders, such as teachers, students, parents and school officials. Apart from that, training is also carried out for teachers in implementing the Independent Curriculum as well as preparing and implementing learning plans that focus on the individual needs of students. Evaluations are carried out periodically to evaluate the effectiveness of implementing this new curriculum. The results of this service are expected to increase students' learning motivation, optimize the use of individual potential, and prepare them to face future challenges.